PRAKTIK JUAL BELI NASKAH DAN UPAYA PELESTARIAN NASKAH MELAYU-MINANGKABAU DI SUMATERA BARAT - Pramono, Pramono (Jurnal Ilmu Budaya, 2009)
The Practice of Selling and Buying old Manuscript has been done is some part in Indonesia. The Buyers are able to buy them in high price.